Actively mode-locked fiber ring laser by intermodal acousto-optic modulation - Bello Jiménez, M. (2010)
We report an actively modelocked fiber ring laser. A simple and low-insertion-loss acoustooptic modulator driven by standing flexural waves -which couples core-to-cladding modes in a standard single-mode optical fiber- is used as active mechanism for modelocking.Among the remarkable features of the modulator we mention its high modulation depth (72 %), broad bandwidth (187 GHz), easy tunability in optical wavelength and low insertion losses (0.7 dB). The narrowest optical pulses obtained were of 95 ps time width, and 21 mW peak power, at a repetition rate of 4.758 MHz.